2022
DOI: 10.3390/cancers14041053
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and pSTAT3 Expression on Circulating Tumor Cells (CTCs) and Immune Cells in the Peripheral Blood of Breast Cancer Patients: Prognostic Implications

Abstract: TLR4 and pSTAT3 are key players in cancer inflammation and immune evasion; however, their role in the peripheral blood (PB) is largely unexplored. Herein we evaluated their expression in the circulating tumor cells (CTCs) and peripheral-blood mononuclear cells (PBMCs) of patients with early (n = 99) and metastatic (n = 100) breast cancer (BC). PB samples obtained prior to adjuvant and first-line therapy, were immunofluorescently stained for Cytokeratins/TLR4/pSTAT3/DAPI and analyzed via Ariol microscopy. TLR4+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…These limitations preclude any valid conclusions about the clinical relevance of specific phenotypic changes in CTCs. In addition, CD45 was not included in the immunofluorescence panel for CTC analysis due to the inability of our method to combine more than four markers (cytokeratins, ALDH1, TWIST1, DAPI); consequently, the identification of CTCs was based on the expression of cytokeratins and morphologic criteria as described in numerous reports from our group and others [ 23 , 24 , 36 , 37 ]. However, our previous studies in independent cohorts of patients with BC and healthy volunteers [ 11 , 13 , 38 , 39 , 40 , 41 ] revealed that there were no cytokeratin+/CD45+ cells evident in the peripheral blood of patients or healthy donors, thus indicating the high specificity of our method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These limitations preclude any valid conclusions about the clinical relevance of specific phenotypic changes in CTCs. In addition, CD45 was not included in the immunofluorescence panel for CTC analysis due to the inability of our method to combine more than four markers (cytokeratins, ALDH1, TWIST1, DAPI); consequently, the identification of CTCs was based on the expression of cytokeratins and morphologic criteria as described in numerous reports from our group and others [ 23 , 24 , 36 , 37 ]. However, our previous studies in independent cohorts of patients with BC and healthy volunteers [ 11 , 13 , 38 , 39 , 40 , 41 ] revealed that there were no cytokeratin+/CD45+ cells evident in the peripheral blood of patients or healthy donors, thus indicating the high specificity of our method.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2 × 10 6 PBMCs (two slides) per patient were analyzed using the automated image analysis Ariol microscopy system and the Ariol system CTCs software (Genetix, Cambridge, UK) [ 23 , 24 , 25 ]. As described in our previous studies, CK expression was used to define CTCs, whereas high ALDH1 expression and nuclear TWIST1 localization were used to define the CSC+ and partial-EMT phenotypes, respectively, on CK+ CTCs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these findings imply that CTCs show enhanced expression of genes that activate survival signals and, in parallel, modulate their interactions with circulating immune cells. It is critical to note here that the mechanisms promoting the immune evasion capacities of CTCs and the tumor–immune crosstalk in the periphery represent a promising field in cancer research, with potential prognostic and therapeutic implications for BC patients [ 14 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%